The chemical composition of the three-part beggarticks (Bidens tripartita L.) - Rodin Mikhail; Potapova Daria; Bokov Dmitrii; Kovaleva Tatiana; Samylina Irina (BIO Web of Conferences, 2023)
In the present article, we have studied the main groups of biologically active substances of the bur-marigold (Bidens tripartita L.) herb using the UPLC method with photodiode array and MS/MS detection. Eighteen compounds have been identified, including the glycosides of luteolin, okaniin, and sulfuretin, polyacetylenes, and hydroxycinnamic acids. The quantitative content of flavonoids (0.7-1.2%) and polysaccharides (4.1-7.5%) was computed by spectrophotometry and gravimetry.